PENINGKATAN KINERJA GURU MELALUI PENGUATAN KECERDASAN SPIRITUAL DI SEKOLAH - Faizin, Faizin; Al Farisi, Yudik; Wafi, Ahmad (Universitas Nurul Jadid, 2021)
This paper presents about improving teacher performance through strengthening spiritual intelligence in schools. This spiritual intelligence is critical to be developed to enhancing the character of PAI teachers for learning tasks. Maintaining Spiritual Intelligence is very influential in forming morals in education to produce education that is broad-minded in the field of science. The research method used by the researcher is a qualitative approach, with data collection techniques through observation, interviews, and documentation, as for analyzing the research data with data reduction, data presentation, and concluding. The results showed that strengthening spiritual intelligence could improve the performance of PAI teachers at SMP Nurul Jadid from the level of discipline, the ability to make lesson plans, mastery of the material, and the ability to master the class. Teachers carry out activities that can support the strengthening of spiritual intelligence, which can improve PAI teachers' quality through habituation, training, and coaching, as well as guidance from caregivers.